The influence of photodynamic therapy parameters on the inactivation of Candida spp: in vitro and in vivo studies - Alves, F. [UNESP]; Mima, E. G. [UNESP]; Dovigo, Lívia Nordi [UNESP]; Bagnato, V. S.; Jorge, Janaina Habib [UNESP]; Souza Costa, C. A. de [UNESP]; Pavarina, Ana Claudia [UNESP] (Iop Publishing Ltd, 2014)
The influence of parameters of photodynamic therapy (PDT), such as pre-irradiation time (PIT), on the inactivation of Candida spp. was assessed in vitro and in vivo. Suspensions of Candida albicans, Candida tropicalis, Candida krusei and Candida glabrata were treated with Photogem (R), incubated for 5, 10 or 15 min and illuminated with a blue LED light. Colonies were cultivated and log values of CFU ml(-1) were analyzed by ANOVA and Kruskall-Wallis test. For in vivo evaluation, immunosuppressed mice were inoculated with C. albicans. PDT was performed on the dorsum of the tongue by topical administration of Photogem (R) and illumination after 5, 10 or 15 min. C. albicans was recovered from the tongue and the number of CFU ml(-1) was analyzed by ANOVA and Tukey test. Animals were killed and the tongues were surgically removed for histological analysis. Susceptibility of Candida spp. suspensions to PDT was in decreasing order: C. albicans = C. tropicalis < C. krusei < C. glabrata. No significant difference was observed among the different PIT (p > 0.05), both in vivo and in vitro. A significant reduction (p < 0.05) of log. CFU ml(-1)) of C. albicans from tongues of mice was observed with no adverse effects in the tissue. PDT was effective to inactivate in vitro Candida spp. and for reduction of C. albicans in vivo, independently of the PIT used.
Keywords: antimicrobial photodynamic therapy; hematoporphyrin derivative; pre-irradiation time; Candida spp.; oral candidiasis; murine model